Application of capacitively coupled contactless conductivity as an external detector for zone electrophoresis in poly(dimethylsiloxane) chips. Issue 3 (27th November 2015) - Koczka, Péter I.; Bodoki, Ede; Gáspár, Attila
Abstract : In this work, lab‐made PDMS microfluidic chips were matched to a capacitively coupled contactless conductivity detector (C 4 D) having external in‐plane electrodes (eDAQ, Australia). The advantages of this type of C 4 D are the choice to reversibly place or remove the microchip onto/from the detector and to freely variate the position of the detection (separation length) on the microchip. The thickness of the bottom layer of the PDMS chip was optimized to achieve sensitive detection during the electrophoretic separation. PDMS chips with 100 μm bottom layer used with the C 4 D platform were tested by CZE of a mixture of seven anions and different types of real samples. Using split‐flow pressure sample injection and effective length of 6.5 cm, the numbers of theoretical plates were in the range of 4000–6000 (63 000–93 000/m) and the LODs amounted to 3.66–14.7 μmol/L (0.13–2.26 μg/mL) for the studied anions.